Building Social Welfare Through Social Security Based on The Socio-Economic Justice During COVID-19 Pandemic Crisis - Muhammad Rafi’i; Zaid Zaid (Institut Teknologi Sepuluh Nopember, 2021)
The purpose of this paper is to examine and analyze based on the principles of social and economic justice on how to grow prosperity during a recession in the midst of the COVID-19 pandemic as it is today through the strategy of providing social security to affected communities. By involving literature review or normative research methods along with a qualitative approach and legislation, this study found that the law on the security system stipulates that social security includes six forms of social security, including health security, work accident security, old-age security, pension security, death security, and job loss security. it's just that the problem is for those who do not pay dues or participate in the government's social security program. Their welfare must also be considered as mandated by the constitution of the 1945 Constitution. And in the principle of socio-economic justice, social security must be prioritized for the poor and underprivileged who are felt to be in more social need to achieve equity and social welfare